2018
DOI: 10.1007/s40615-018-0460-7
|View full text |Cite|
|
Sign up to set email alerts
|

Power of Peer Support to Change Health Behavior to Reduce Risks for Heart Disease and Stroke for African American Men in a Faith-Based Community

Abstract: Qualitative findings revealed a positive perception of peer support and greater understanding of potential reasons why it may be an effective strategy for African American men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…• settings-and place-based health promotion approaches, with a particular focus on engagement through faith-based settings, [117][118][119] barber shops, 120,121 sports clubs/organisations, 83 and colleges and universities; 82,[122][123][124] • strategies that explicitly address healing, intergenerational trauma and racism; 61,101,[125][126][127][128][129][130] • involving peers and family; 84,131,132 • strengths-based approaches that focus on achievement, success and building leadership capacity; 133,134 and • approaches that address specific health issues, such as mental health and wellbeing and respective mechanisms associated with coping and resilience. 82,84,103,104,123 Importantly, there are now multiple organisations, services and programs that exist to address health and social inequities experienced by boys and young men of colour.…”
Section: Race and Gendermentioning
confidence: 99%
“…• settings-and place-based health promotion approaches, with a particular focus on engagement through faith-based settings, [117][118][119] barber shops, 120,121 sports clubs/organisations, 83 and colleges and universities; 82,[122][123][124] • strategies that explicitly address healing, intergenerational trauma and racism; 61,101,[125][126][127][128][129][130] • involving peers and family; 84,131,132 • strengths-based approaches that focus on achievement, success and building leadership capacity; 133,134 and • approaches that address specific health issues, such as mental health and wellbeing and respective mechanisms associated with coping and resilience. 82,84,103,104,123 Importantly, there are now multiple organisations, services and programs that exist to address health and social inequities experienced by boys and young men of colour.…”
Section: Race and Gendermentioning
confidence: 99%
“…The study results indicated that discussions among participants may be key to intervention implementation and adaptation. Discussions between peers sharing in a recovery program can encourage individuals to jointly identify ways to adapt content to fit lifestyles and individual needs (Lee et al, 2018). In addition, studies of educational interventions with peer support are known to be an effective and cost-efficient method of improving health outcomes (Krishnamoorthy et al, 2019).…”
Section: Elements Quotesmentioning
confidence: 99%
“…In addition, studies of educational interventions with peer support are known to be an effective and cost-efficient method of improving health outcomes (Krishnamoorthy et al, 2019). Social support is a commonly cited component of improved health outcomes for individuals, reducing the risk of CHD (Lee et al, 2018), and for those in rehabilitation programs (Wobma et al, 2016). Conflicting and inconclusive evidence is present when examining overall effectiveness of peer support interventions to improve physical function (Burton et al, 2018).…”
Section: Elements Quotesmentioning
confidence: 99%
“…Peer group support can be used to build strong social relationships, as well as provide social support and networking. Indeed, peer group support interventions have been used to foster healthy behaviour changes in several studies (Lee et al., 2018b; Okoro et al., 2018). One such study reported that team-based interventions that utilised groups of peers provided strong networks that positively influenced health behaviour change for weight loss (Leahey et al., 2012).…”
Section: Introductionmentioning
confidence: 99%